Unveiling river-groundwater interactions through time-variable seismic velocity in northern Pingtung Plain, southern Taiwan - Tzu-Yi Lien; Emmy Tsui-Yu Chang; Hou-Sheng Cheng; Ta-Kang Yeh (Journal of Hydrology: Regional Studies)
Study region: The Ailiao-Laonong river basin in the northern Pingtung Plain, Taiwan. Study focus: Probing groundwater in the Pingtung Plain is essential because of water shortages and rising water demand. The feasibility of artificial groundwater recharge has been investigated through seismic velocity variations. This study employed an innovative and cost-effective seismological approach to examine the responses of river and groundwater recharge, and to evaluate recharge constructions associated with a dredging project conducted in southern Taiwan in 2023. Seismic velocity changes (dv/v) were determined from four years of continuous seismic data applying seismic interferometric analysis and cross-correlation functions (CCFs) between seismic stations to reconstruct an ambient seismic wavefield. Uneven coherence responses along the causal and acausal axes of the CCFs can be used to determine the direction of signal propagation within the wavefield. New hydrological insights for the region: We firstly show the temporal alteration of CCF responses along the direction of station pairs across rivers. Larger response amplitudes of causal and acausal of the CCFs indicated the ambient noise sources are aligned with groundwater transport directions in the Ailiao-Laonong basin. Seismic pairs across the Laonong River exhibited flow direction changes during the rainy season (June to September), revealing groundwater and river water exchanges in this area. Amplified source signals present the enhancing recharge from the north bank of Ailiao Creek during typhoon season. These findings suggest that the optimal period for groundwater recharge is from June to September, with construction completion ideally by June. Results show that during the dry season, the primary source of groundwater recharge is from the east mountain, whereas during the wet season, the recharge source is predominantly from the north. This study demonstrates the alternating process of recharging and drainage between groundwater and river water levels.